Sequential processing with fermentative Caldicellulosiruptor kronotskyensis and chemolithoautotrophic Cupriavidus necator for converting rice straw and CO2 to polyhydroxybutyrate. Issue 6 (13th March 2018) - Peng, Xiaowei; Kelly, Robert M.; Han, Yejun
Abstract: Unpretreated rice straw was fermented by the extremely thermophilic bacterium Caldicellulosiruptor kronotskyensis, generating solubilized carbohydrates, organic acids, lignin‐derived aromatics, H2, and CO2, which were subsequently used to produce polyhydroxybutyrate (PHB) by the chemolithoautotrophic bacterium Cupriavidus necator . The fermented liquid significantly enhanced the growth of C. necator, leading to a five‐fold cell biomass yield, and a nine‐fold PHB yield compared to what was obtained from conventional mineral media. This integrated process utilized all products of lignocellulose fermentation without H (electron) loss and carbon emission, while concomitantly enhancing CO2 fixation by C. necator for PHB production. The sequential coupling of C. kronotskyensis and C. necator provides not only a new biorefinery paradigm characterized by reduced pretreatment and saccharification requirements but also an efficient way for enhancing CO2 fixation. Abstract : A novel sequential processing with fermentative Caldicellulosiruptor kronotskyensis and chemolithoautotrophic Cupriavidus necator for converting unpretreated straw and CO2 to polyhydroxybutyrate was developed. This integrated process utilized all products of lignocellulose fermentation without H (electron) loss and carbon emission, while concomitantly enhancing CO2 fixation by C. necator for PHB production. This research suggests a cost effective and environmentally benign way for biochemicals and biofuels production from lignocellulosic biomass and CO2 .